Updates of the In‐Gel Digestion Method for Protein Analysis by Mass Spectrometry. Issue 23 (25th November 2018) - Goodman, Jennifer K.; Zampronio, Cleidiane G.; Jones, Alexandra M. E.; Hernandez‐Fernaud, Juan R.
Abstract: The in‐gel digestion of proteins for analysis by liquid chromatograph mass spectrometry has been used since the early 1990s. Although several improvements have contributed to increasing the quality of the data obtained, many recent publications still use sub‐optimal approaches. Updates of the in‐gel digestion protocol has been presented in the study. It has been shown that alternative reducing, alkylating agent reactions, and tryptic digestion buffers increase peptide and protein identification and reduce incubation times. The results indicate that a simultaneous and short, high temperature reduction and alkylation reaction using Tris(2‐carboxyethyl)phosphine hydrochloride and chloroacetamide with a subsequent gel wash improve protein identification and sequence coverage, and diminish peptide side reactions. Additionally, use of 4‐(2‐hydroxyethyl)piperazine‐1‐ethanesulfonic acid buffer allows a significant reduction in the digestion time improving trypsin performance and increasing the peptide recovery. The updates of the in‐gel digestion protocol described here are efficient and offer flexibility to be incorporated in any proteomic laboratory.